Detection of Fusarium oxysporum Fungal Isolates Using ATR Spectroscopy. Issue 5 (11th July 2012) - Salman Salman, A. A.; Lapidot Lapidot, I. I.; Pomerantz Pomerantz, A. A.; Tsror Tsror, L. L.; Hammody Hammody, Z. Z.; Moreh Moreh, R. R.; Huleihel Huleihel, M. M.; Mordechai Mordechai, S. S.
Abstract : Fungi are considered as serious pathogens for many plants, potentially causing severe economic damage. Early detection and identification of these pathogens is crucial for their timely control. The methods available for identification of fungi are time consuming and not always very specific. In this study, the potential of FTIR-ATR spectroscopy was examined together with advanced mathematical principle component analysis (PCA) and statistical linear discriminant analysis (LDA) to differentiate among 10 isolates of Fusarium oxysporum. The results are encouraging and indicate that FTIR-ATR can successfully detect different isolates of Fusarium oxysporum. Based on PCA and LDA calculations in the region 850–1775 cm −1 with 16 PC's, the different strains from the same fungal genus could be classified with 75.3% and 69.5% success rates using the "leave one out" method and "20–80% algorithm" respectively.